Skin Metabolic Signatures of Psoriasis and Psoriasis Concurrent with Metabolic Syndrome - Yan L; Wang W; Dong M; Wang R; Li C (Journal of Inflammation Research)
Liang Yan,1,2 Wenqiu Wang,1 Meihan Dong,1 Rui Wang,1 Chengxin Li1,3 1Department of Dermatology, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China; 2Department of Dermatology, General Hospital of Central Theater Command of PLA, Wuhan, 430070, People’s Republic of China; 3State Key Laboratory of Kidney Diseases, National Clinical Research Center for Kidney Diseases, Beijing, 100853, People’s Republic of ChinaCorrespondence: Chengxin Li; Rui Wang, Department of Dermatology, The First Medical Center of Chinese PLA General Hospital, No. 28, Fuxing Road, Haidian District, Beijing, 100853, People’s Republic of China, Tel +86-01066939315 ; +86-01066939314, Email chengxinderm@163.com; wr0699@163.comPurpose: Psoriasis is a complex inflammatory skin disorder that is closely associated with metabolic syndrome (MetS). Limited information is available on skin metabolic changes in psoriasis; the effect of concurrent MetS on psoriatic skin metabolite levels is unknown. We aimed to expand this information through skin metabolomic analysis.Patients and Methods: Untargeted metabolomics was conducted using skin samples from 38 patients with psoriasis vulgaris with MetS (PVMS), 23 patients with psoriasis vulgaris without MetS (PVNMS), and 10 healthy controls (HC). Data analyses, including multivariate statistical analysis, KEGG pathway enrichment analysis, correlation analysis, and receiver operating characteristic curve analysis, were performed.Results: Significant discrepancies were found between skin metabolites in the HC and PVNMS groups, particularly those involved in nucleotide and glycerophospholipid metabolism. Fifteen of these metabolites were positively correlated with psoriasis severity. Furthermore, MetS was found to affect the metabolic profiles of patients with psoriasis. There were some metabolites with consistent alterations in both the PVNMS/HC and PVMS/PVNMS comparisons.Conclusion: This study may provide new insights into the link between skin metabolism and psoriatic inflammation and the mechanism underlying the interaction between psoriasis and MetS.Keywords: psoriasis, metabolic syndrome, metabolomics, nucleotide metabolism, glycerophospholipid metabolism